Treaty between the United States and the Blackfoot and other tribes of Indians - Blackfeet Tribe of the Blackfeet Indian Reservation of Montana
Typewritten transcript of a treaty stipulating land for homes and hunting grounds for the Blackfoot or Blackfeet (Sihasapa) and other Indian tribes in the Nebraska Territory. Signatories include Franklin Pierce and William L. Marcy.
Three additional typescripts available.
Typewritten transcript.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Marcy, William L. -- 1786-1857.; Pierce, Franklin, -- 1804-1869.; Indians of North America -- Government relations; Indians of North America -- Nebraska; Indians of North America -- Treaties; Sihasapa Indians; Nebraska -- History